Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) untuk Meningkatkan Kemampuan Berfikir Kritis Siswa di Sekolah Dasar - Nuraeni, Yeni; Fahtoni, Arbillah; Syfa, Delia; Agustin, Elsa Rizqina; Lubis, Rahma Dani; Azzahra, Radiva Samsa (Lembaga Yasin AlSys, 2025)
The study examines the implementation of the Strengthening the Profile of Pancasila Students Project (P5) in elementary schools and its impact on students' critical thinking abilities. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The findings indicate that P5, as part of the Merdeka Curriculum, effectively fosters critical thinking skills by engaging students in project-based learning activities rooted in Pancasila values. This approach enables students to identify problems, analyze information, evaluate solutions, and make rational decisions.The study identifies supporting factors, such as teacher facilitation, parental involvement, and a conducive learning environment, alongside challenges, including resource limitations, time constraints, and inadequate teacher training. To address these obstacles, continuous teacher training and enhanced school-community collaboration are recommended. The research underscores the potential of P5 to be widely adopted in elementary education, emphasizing the need for comprehensive project-based assessment models.